PENGANGGURAN STRUKTURAL DI INDONESIA: KETERANGAN DARI ANALISIS SVAR DALAM KERANGKA - Dharendra Wardhana; Dhanie Nugroho (Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
This paper is mainly aimed to measure labor supply shocks and their effects to national economy through “theory-guided view” mechanism by using such indicators as unemployment rate, real Gross Domestic Product, and real wages. By implementing structural VAR methodological framework, it makes possible to trace and to identify how an economy works through imposing restrictions in order to conform to theory. Our results suggest that long-term unemployment affected the process of policy making of both monetary and real sector in achieving objectives set in national development planning.